(untitled) ("Journal "U". Economy. Management. Finance.", 2021)
The article discusses the concept of a strategic management mechanism and defines their types. As part of the study, the essence of each of the proposed mechanisms was considered and the possibility of their application in real estate agencies was analyzed.